2013
DOI: 10.1155/2013/461365
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid and BSA Protein in Solution and Films: Interaction and Surface Morphological Structure

Abstract: This paper reports on the study of the interactions between ascorbic acid (AA) and bovine serum albumin (BSA) in aqueous solution as well as in films (BSA/AA films) prepared by the layer-by-layer technique. Regarding to solution studies, a hyperchromism (in the range of ultraviolet) was found as a function of AA concentration, which suggested the formation of aggregates from AA and BSA. Binding constant, K, determined for aggregates from BSA and AA was found to be about 102 M−1, which indicated low affinity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Fig 5 shows second derivative FT-IR spectra from the dried EMD-buffer solutions (cf. the images in Figs 1 and 3 ) in the wavenumber range corresponding to the amide I band, suggesting primarily mixed β-sheet and β-turn structure [ 45 ]. Thus, spectra obtained from the specimens prepared at pH 2 ( Fig 5(a) ), an intramolecular β-sheet peak was visible at 1633 cm -1 and the peaks at 1660, 1668 and 1675 cm -1 were assigned to β-turns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig 5 shows second derivative FT-IR spectra from the dried EMD-buffer solutions (cf. the images in Figs 1 and 3 ) in the wavenumber range corresponding to the amide I band, suggesting primarily mixed β-sheet and β-turn structure [ 45 ]. Thus, spectra obtained from the specimens prepared at pH 2 ( Fig 5(a) ), an intramolecular β-sheet peak was visible at 1633 cm -1 and the peaks at 1660, 1668 and 1675 cm -1 were assigned to β-turns.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 1683 was associated with β-turns/intermolecular β-sheets and there was a further intermolecular β-sheet peak at 1698 cm -1 . The peaks at 1643 and 1652 cm -1 were assigned to random coils and random coils/α-helices, respectively, and the peak at 1620 cm -1 was tentatively identified with polyproline II helix structure, based on previous observations of aqueous amelogenin at different pH [ 12 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The UV-Vis spectroscopy technique is a simple and effective method to investigate the molecular interaction and complex formation [ 21 ]. UV-Vis analyses were performed for BSA in solution with physiological pH and concentration of 1.9 × 10 −6 mol·L −1 (required for better visualization of the band at 278 nm) and modified solution after the addition of Chl at different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of studies on interaction of BSA and ligands have been carried out. In these works, compounds including 2-(4-N,N-dimethylamino) phenylimidazo [4,5-b]pyridine (DMAPIP-b) [ 10 ], imidazolium chloride ionic liquids [ 11 ], prednisolone [ 12 ], aspirin [ 13 ], resveratrol [ 14 ], genistein [ 14 ], curcumin [ 14 16 ], malachite Green [ 17 ], bright red 6C [ 18 ], anticancer drugs [ 19 ], heparin [ 20 ], and ascorbic acid [ 21 ] were used. In particular, the behavior of the binding of chlorophyll (Chl) to BSA has been also examined [ 22 ] because it has been shown that this ligand can exhibit antimutagenic property against several potential human carcinogens [ 23 , 24 ], action antioxidant [ 25 ], and antigenotoxic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation